MENGUKIR KOMPETENSI DIGITAL : STUDI KASUS PELATIHAN MICROSOFT EXCEL DALAM MENINGKATKAN KETERAMPILAN PENGOLAHAN DATA SISWA - Afrizal Rizqy Pratama; Zaehol Fatah (Jurnal Riset Teknik Komputer, 2025)
This study aims to assess the extent to which Microsoft Excel training is expected to improve the information processing skills of students in Madrasah aliyah (MA) Sunan Ampel, Sumberkima, Buleleng, Bali. Through a case study approach, we examine how this training successfully sculpts advanced-level students’ competencies, transforming them from passive users into individuals fluent in processing information. A curriculum focused on practical applications Exceeding expectations , ranging from basic functions to simple information visualization, is proven to significantly improve students’ ability to sort, analyze, and present information. The method applied in this study was a practice-based training, followed by an assessment of the skills of the participants after the training. The research findings indicated that microsoft training exceeded expectations was able to significantly improve students’ information retrieval skills, accelerating the process of information recapitulation and analysis. However, it was found that a proportion of participants still required individual assistance to achieve full mastery on the more advanced features. Overall, this training had a positive influence on improving information processing skills in Madrasah Aliyah (MA) Sunan Ampel Sumberkima, Buleleng, Bali. as well as can be an initial step to optimize the utilization of technology in educational information processing.